Development aid from the CMEA countries and the People's Republic of China - Heinrich Machowski; Siegfried Schultz (Intereconomics, 1979)
At UNCTAD V not only the Western industrialised countries but also the socialist states were heavily criticised for not appropriating sufficient funds for development aid. The following article presents a survey of volume, conditions, and regional distribution of the CMEA countries' and the PR China's aid on the basis of recent estimates.
Keywords: 330